Independence in some Grammatical Opinions and Evidence among Modern Scholars Selected Samples - الصُّويلح, محمَّد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The observer will find in the previous opinions that contemporary grammatical scholars have striven to achieve independence with some opinions and evidence that sought to be unique and distinguished in some unprecedented aspects. Some of these opinions were based on what was present in the nation’s heritage, but on the part of these scholars, this characteristic remained partial and useless and it was not a widespread phenomenon in their work as this independence requires a complete study of the issue to be dealt with, and being aware of all its historical and contextual aspects, so that the opinions are based on sound foundations, without deficiency or contradiction.